Investigating the Relationship between SHRM and Organizational Performance by Mediating Role of Management Capability and Entrepreneurial Orientation (Case Study: Veterinary Medicine Office of Hamedan Governorate - Mehdi Ajalli; Ehsan Hemmati (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The current research investigated the relationship between strategic human resource management and organizational performance with the mediating role of managerial ability and entrepreneurial orientation.Methodology: This research is a survey regarding the data collection method. The research method is a description of the correlation type, and the statistical population of the study includes all the employees of the General Veterinary Department of Hamedan province in 2016, numbering 150 people according to Cochran's formula, the statistical sample size is approximately equal to 98 people who were selected by simple random sampling. A structural equation modelling approach and path analysis method with SPLS software were used to analyze the research data.Findings: The results of the confirmatory factor analysis test and the measurement of factor loadings showed that the strategic human resource management variable accounted for 74% of organizational performance changes, strategic human resource management accounted for 67% of managerial capability changes, and strategic human resource management accounted for 57% of It explains changes in entrepreneurial focus. Also, managerial ability explains 58% of organizational performance changes, and entrepreneurial orientation explains 48% of organizational performance changes. Finally, organizational performance is 63% due to changes in financial performance and 52% due to changes in employee performance. Also, with the test of significant Z coefficients (t values), it was found that the coefficient related to all paths, including the paths of strategic management of human resources to managerial ability (5.469), strategic management of human resources to entrepreneurial orientation (4.748), strategic management of resources Humanity to organizational performance (7.387), managerial ability to organizational performance (5.294) and entrepreneurial orientation to organizational performance (6.374) are more than 1.96, indicating the significance of these paths and the appropriateness of the structural model.Originality/Value: The present study indicates that the strategic management of human resources directly has a more significant impact on organizational performance (compared to the variables of managerial ability and entrepreneurial orientation). The results showed that financial performance has a more significant effect on organizational performance.